Analysis of Motor Vehicle Tax Revenue (PKB) in Increasing Local Revenue (PAD) of Jambi Province for The Period 2018-2022 - Dewi Safitri; Nyayu Fadilah; Friska Artaria (Accounting Journal of Ibrahimy (AJI), 2025)
Taxes were a very important state source that supports development programs and is sourced from within the country. This study aimed to analyze and determine the acceptance of motor vehicle tax (PKB) in increasing Jambi Province's local revenue (PAD) for the 2018-2022 period. This research was narrative with a descriptive approach, using secondary data. The data processed was PKB revenue data and PAD for the 2018-2022 period obtained from the Jambi Province Regional Financial and Revenue Management Agency (BPKPD). This study used data analysis by calculating the effectiveness of PKB revenue realization and the level of PKB contribution in increasing local revenue. Based on the results of the study, during the 2018-2022 period the average level of effectiveness of PKB revenue was 106.40%. And the contribution of PKB amounted to 28.15%. Besides the high level of effectiveness of PKB revenue, there were obstacles in PKB revenue due to lack of public awareness of motor vehicle taxes.